Mean Glandular Dose from Routine Mammography - Sookpeng, Supawitoo; Ketted, Potjana (Asian Health, Science and Technology Reports, 2006)
A mammography examination facilitates the early detection of breast cancer. However, the potential risk of radiation-induced carcinogenesis is also increased with such a procedure. The objective of this research was to measure the mean glandular dose (MGD) from craniocaudal (CC) and mediolateral oblique (MLO) views in each breast and the total dose per woman (for both breasts and two views) from the exposure factor in patients undergoing mammography on six mammography x-ray generators in the lower region of northern Thailand. The values of compressed breast thickness (CBT), as well as the MGD calculated from the exposure and tube voltage both mAs and target/filter combination, were collected from 2,060 films from 515 women ranging in age from 28 to 91 years. Significant differences were found between MGD from CC and MLO projections. The MGD per film was 1.42+0.80 mGy for the CC projection and 1.56+0.86 mGy for the MLO projection, (p<0.001). The MGD per CC and MLO film was significantly related to CBT (r = 0.610, p<0.01 and r = 0.596, p<0.01 respectively). The result indicated that 96.1 % of CC films and 94.2 % of MLO films had doses less than 3.0 mGy as recommended by the American College of Radiology recommendations. This may ensure that the mammography examination in the lower region of northern Thailand is capable of achieving acceptable dose levels for patient safety.